Implementation of Permenkes Number 82 of 2013 Concerning Hospital Management Information Systems (SIM RS) (Study at Kertosono Regional Hospital, Nganjuk Regency) - Wafidah, Anisatul; Marwanto, I Gusti Gede Heru; Pramono, Teguh; Muzaqi, Ajie Hanif (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2023)
This study is intended to analyze and describe the implementation of Permenkes Number 82 of 2013 concerning Hospital Management Information Systems (SIRS) at the Kertosono Regional Hospital, Nganjuk Regency using the theory of George C Edward III, namely communication, energy sources, dispositions and bureaucratic structures. Procedures in research are descriptive qualitative procedures. The research data sources were selected purposively and snowball sampling. The data were collected using observation, interviews, and documentation and then the data was processed using condensation, presentation and drawing conclusions. lack of communication and outreach from the implementor. In order to overcome the constraints, the implementer can develop a socialization program so that communication can run and it is necessary to determine rewards and punishments for procedural compliance in order to improve the quality of data that influences decision making. The impact felt by this research was the training of staff and employees of RSD Kertosono to increase knowledge of the application of SIMRS.